Implementing the Alumni-Unicamp platform: A case study - Kassisse, Dora Maria Grassi (ICAReAlumni Conference Proceedings, 2023)
Pro- Rectory Undergraduate Strategic Project Alumni UNICAMP We idealize products: Egress Portal Graduate Management Process Evaluation Mechanisms of and by the Graduate Policies and Mechanisms for attracting and applying Financial Resources Expected gains from this project .Expand/qualify permanence .Decreased Evasion .Expand dialogue with society .Increase in extrabudgetary resources .Increased visibility of the University .Enrichment of student training